Determination of nanoparticle force balance in an electrical magnetic separation system - E.E. Volkanin (National Technical University "Kharkiv Polytechnic Institute", 2014)
Analytical expressions for magnetic force gradient computation are given. FEM simulation of the matrix core in the working gap of a magnetic system is conducted. The magnetic force distribution is presented as a relative ratio. A force balance equation taking into account the magnetic force pattern is derived.